2016
DOI: 10.1111/resp.12900
|View full text |Cite
|
Sign up to set email alerts
|

Variability of breathing during wakefulness while using CPAP predicts adherence

Abstract: At the initiation of therapy, breathing regularity during wakefulness while wearing CPAP is an objective predictor of short-term CPAP adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…15,43 Despite the emerging evidence suggesting that physiologic OSA traits can predict response to CPAP-alternative treatments (ie, oral appliances, upper airway surgery), 44,45 little is known about whether these traits affect CPAP tolerance or adherence. Fujita et al 46 showed that increased breathing irregularity while awake (defined by coefficient of variation in tidal volume > 34.0) predicted poor CPAP adherence at 1 month. Gray et al assessed the ArTH in a small group of patients with OSA who were recommended to receive CPAP treatment (n = 94), 14 and in multivariate analyses a low ArTH was not associated with CPAP use at follow-up (up to 22 months).…”
Section: Implications For Cpap Use and The Interaction With Obesitymentioning
confidence: 99%
“…15,43 Despite the emerging evidence suggesting that physiologic OSA traits can predict response to CPAP-alternative treatments (ie, oral appliances, upper airway surgery), 44,45 little is known about whether these traits affect CPAP tolerance or adherence. Fujita et al 46 showed that increased breathing irregularity while awake (defined by coefficient of variation in tidal volume > 34.0) predicted poor CPAP adherence at 1 month. Gray et al assessed the ArTH in a small group of patients with OSA who were recommended to receive CPAP treatment (n = 94), 14 and in multivariate analyses a low ArTH was not associated with CPAP use at follow-up (up to 22 months).…”
Section: Implications For Cpap Use and The Interaction With Obesitymentioning
confidence: 99%
“…Some progress has been made in this area with surrogate measures of physiological traits discernible from awake breathing measures, PSG data and therapeutic CPAP levels . Similarly, breathing regularity during CPAP acclimation is predictive of subsequent CPAP adherence . This phenotypic approach to OSA holds the possibility of altering our assessment and treatment paradigm and fits in well with the P4 approach to personalized health care (Fig.…”
Section: Sleepmentioning
confidence: 58%
“…Our study indicates that the granularity concept applied to respiratory rate quantification and abnormal pattern prediction might provide novel insights into cardiorespiratory regulation beyond those offered by a simple analysis of respiratory rate, inspiration and expiration times, tidal volume assessment, or their variability [ 48 , 49 ]. Many previous studies concerning respiratory variability have been performed in animals and cannot be directly translated to humans [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%